2013
DOI: 10.1371/journal.pone.0060577
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Dynamics and Potential Annual Fecundity of South Pacific Albacore Tuna (Thunnus alalunga)

Abstract: The reproductive biology of albacore tuna, Thunnus alalunga, in the South Pacific Ocean was investigated with samples collected during broad-scale sampling between 2006 and 2011. Histology was done in a single laboratory according to standard protocols and the data analysed using generalized linear mixed-effects models. The sex ratio of albacore was female biased for fish smaller than approximately 60 cm FL and between 85 and 95 cm, and progressively more male biased above 95 cm FL. Spawning activity was synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 15 publications
6
85
3
4
Order By: Relevance
“…Sex ratios reported for other tuna species are generally 1∶1 with a similar prevalence of males in the larger length classes [25]. The male dominance in large length classes for SBT may be due to the observed sexual dimorphism in growth, as suggested for albacore tuna ( Thunnus alalunga ) in the South Pacific Ocean [26].…”
Section: Discussionmentioning
confidence: 83%
“…Sex ratios reported for other tuna species are generally 1∶1 with a similar prevalence of males in the larger length classes [25]. The male dominance in large length classes for SBT may be due to the observed sexual dimorphism in growth, as suggested for albacore tuna ( Thunnus alalunga ) in the South Pacific Ocean [26].…”
Section: Discussionmentioning
confidence: 83%
“…Dufour [20] showed that the feeding migration of the offshore longitudinal distribution of albacore tuna in the Bay of Biscay was related to the warmer 17˚C isotherm longitude from 1967 to 2005. Farley [41] showed that the peak spawning of albacore tuna in the South Pacific Ocean occurred from October to December [43]. PWI most likely affects the prey abundance and distribution as well as the spawning stages for the younger portion of the albacore tuna stock harvests in the South Pacific Ocean where major part of the harvested stock ranges from 2 to 4 years olds [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although much of this variability remains unexplained, tuna abundance in space and time has been correlated with factors including oceanographic conditions, physiological constraints (e.g. temperature, depth, oxygen requirements), forage availability, and reproductive behavior (Farley et al, 2013;Senina et al, 2008;Young et al, 2011).…”
Section: Introductionmentioning
confidence: 99%